Three dimensional (3D) failure pattern of flexible pile due to lateral cyclic loading in sand - M. F. Awad-Allah; N. Yasufuku; S. Manandhar (International Association of Lowland Technology, 2017)
In this paper, a set of small-scale laboratory single flexible pile model was conducted in a medium dense Toyoura sand environment under the effect of cyclic lateral loads. Digital images were captured for the plastic deformations of the soil during the lateral loading from the top of the testing chamber. Combination of photo image analysis and analytical cyclic p-y curve methods was implemented for estimating the three dimensional (3D) failure zone adjacent to pile shaft. The 3D failure pattern of the soil around single pile shaft was investigated through two steps, including: (1) determination of the range of lateral plastic deformations at the top of ground surface in perpendicular and parallel directions of cyclic loads; and (2) determination of the point of rotation (zero displacement) along the pile shaft. Experimental results showed that a conical passive zone of plastic deformations is established around pile shaft due to applying two-way lateral cyclic loading at pile head. Based on the findings, design considerations for piles subjected to lateral cyclic loading have been introduced.